The Ecology of Space - Sztumski, Wiesław (Problemy Ekorozwoju, 2011)
The subject of the ecology of space is basically the social space. It also includes the physical space only in so far as it is part of the social space and directly interacts with it. The structure of social space is complex. It contains a set of social sub-spaces and related landscapes. The landscape is defined as a subjective perception of objective space. The paper presents descriptions of some social landscapes (physical, urban, acoustic, axiological, and virtual landscapes as well as the landscapes of faith, truth and communication) in respect of their degeneration caused by Western culture, liberalism and the ideology of consumerism. That should entitle the need for the care of social landscapes within the ecology of space.